Answer:
(x, y) → (x + 4, y - 3)
Explanation:
If a point (x, y) is translated by 'a' units to the right and 'b' units down, new coordinates of the image point will be,
(x', y') → (x + a, y - b)
By applying this rule in the picture attached,
Coordinates of A → (-4, 2)
Coordinates of A' → (-4 + a, 2 - b)
Since, coordinates of A' are (0, -1)
Therefore, (-4 + a, -2 - b) = (0, -1)
Comparing coordinates on both the sides,
-4 + a = 0 ⇒ a = 4
2 - b = -1
b = 3
Therefore, rule for the translation will be,
(x, y) → (x + 4, y - 3)